The effects of hypoxia and fatigue on skeletal muscle electromechanical delay - Jacunski, M.; Rafferty, G. F. (Experimental Physiology, 2020)
New Findings " What is the central question of this study? The mechanisms underlying impaired muscular endurance and accelerated fatigue during acute hypoxia are incompletely understood. Hypoxia may affect neuromuscular transmission and the muscle membrane, slowing the propagation of myopotentials, compromising excitation-contraction coupling and resulting in premature fatigue " What is the main finding and its importance? Hypoxia had no effect on the electrochemical latency associated with muscle contraction elicited by supramaximal electrical motor nerve stimulation in vivo. These data provide greater insight into the effects of hypoxia and fatigue on the mechanisms of muscle contraction in vivo. Abstract Acute hypoxia impairs muscle endurance and accelerates fatigue, but the underlying mechanisms, including any effects on muscle electrical activation, are incompletely understood. Electromyographic, mechanomyographic and force signals, elicited by common fibular nerve stimulation, were used to determine electromechanical delay (EMDTOT) of the tibialis anterior muscle in normoxia and hypoxia (FiO2 0.125) at rest and following fatiguing ankle dorsiflexor exercise (60% maximum voluntary contraction, 5 seconds on, 3 seconds off) in 12 healthy participants (mean (SD) age 27.4 (9.0) years). EMDTOT was determined from electromyographic to force signal onset, electrical activation latency from electromyographic to mechanomyographic (EMDE-M) and mechanical latency from mechanomyographic to force (EMDM-F). Twitch force fell significantly following fatiguing exercise in normoxia (46.8 (14.7) vs 20.6 (14.3) N, p = 0.0002) and hypoxia (52.9 (15.4) vs 28.8 (15.2) N, p = 0.0006). No effect of hypoxia on twitch force at rest was observed. Fatiguing exercise resulted in significant increases in mean (SD) EMDTOT in normoxia (Delta 4.7 (4.57) ms p = 0.0152) and hypoxia (Delta 3.7 (4.06) ms p = 0.0384) resulting from increased mean (SD) EMDM-F only (normoxia Delta 4.1 (4.1) ms p = 0.0391, hypoxia Delta 3.4 (3.6) ms p = 0.0303). Mean (SD) EMDE-M remained unchanged during normoxic (Delta 0.6 (1.08) ms) and hypoxic (Delta 0.25 (0.75) ms) fatiguing exercise. No differences in percentage change from baseline for twitch force, EMDTOT, EMDE-M and EMDM-F between normoxic and hypoxic fatigue conditions were observed. Hypoxia in isolation or in combination with fatigue had no effect on the electrochemical latency associated with electrically evoked muscle contraction.